Speech Etiquette In Russian And Uzbek Languages - Ildar Urakovich Khatamov (Periodica Journal, 2026)
The rules of etiquette are not only norms of behavior in society, but also the ability to correctly express one's thoughts. This is the beauty of speech and its content, as well as the use of phrases depending on the situation.
Keywords: culture of speech; etiquette; communication